How good are the examination findings in predicting the chest radiographic abnormalities amongst children with LRTI? - Goel, Ishank; Kher, Anjali; Vagha, Jayant (International Journal of Contemporary Pediatrics, 2016)
Background: Acute lower respiratory tract infections are an important cause of mortality and morbidity in children below five years of age. Plain chest radiograph remains the most accessible and commonly used radiological tool. The present study is thus designed to clinically evaluate children with pneumonia, to identify the risk factors and correlate them with the X-ray findings. Methods: Our study was an observational and Analytical study. A total of 250 patients from the age group of 2 months to 5 years, admitted in paediatrics wards with respiratory complaints suggestive of involvement of lower respiratory tract whose X-rays were done were included in our study. All the patients were examined by the clinical experts every day and the findings were being confirmed by at least two experts. Radiologists/residents in the department made the first assessment during their daily practice through online database. The radiologist, who was not informed about the results of the first assessment, re-examined the radiographs. X-ray findings were then compared with clinical features. Results: Out of 250 children, 137 patients had normal radiographs and 113 had abnormal radiographs. Pallor, intercostal retractions, subcostal retractions, grunt, nasal flaring, decreased breath sounds and crepts had a sensitivity of 80.53%, 84.07%, 76.99%, 70.80%, 76.99%, 73.45%, 62.83% and specificity of 30.66%, 35.77%, 67.88%, 82.48%, 36.50%, 88.32%, 49.64% respectively, in predicting the chest X-ray abnormalities in LRTI. Conclusions: Tachypnea, pallor, retractions, grunt, nasal flaring, decreased breath sounds and crepitations were the main indicators of ALRI confirmed by X-ray. Inspection and Auscultation were two more important pillars of Respiratory system examination in children, where we could predict abnormal X-ray findings.